Perbandingan Konsepsi Epistemologi Empirisisme Ibnu Taymiyyah dan John Locke - Rido Kurnianto (TSAQAFAH, 2014)
This paper examined the epistemological empiricism conception of Ibn Taimiyyah and John Locke based on the comparative analysis to obtain the complete description of epistemological empiricism thought of both, as well as its implications and consequences for the development of science and religious thought. To obtain the detailed answer about the two figures thought, it would be revealed the similarities and differences of epistemological empiricism of each by showing the elements that became the focus of both studies. Furthermore, from those, it will be sought the strange and weaknesses, and possible relevance of the two thought to find a new alternative as a reflective systematic model for the development of science and religious thought in the present and future. Comparing the empirical thought of both figures above is important to do, due to the empirical tradition in the two mens’ world have a very extreme differences. In the west, Empiricism had contributed significantly to the epistemological assets or legacy and had led to the development of science and technology. In contrast, empiricism in the east, was suspected as a harmful tradition to the Islamic ideology. It was considered as the seed that gave birth to atheism. Based on the two thinkers empiricism, will appear the strategic idea that can be synthesized to developed modern science as well as Islamic thought. Bot of epistemology thought can be combine to reconstruct the Islamic epistemology which is more open and more mature, because in that context will emerge the theories of knowledge without eliminating the metaphysical and ethical authority. In the context of combination, the natural tendency of foundation of Islamic teaching should be the bases of policy as descript by Ibnu Taimiyyah, that human nature becomes the foundation of the human responsibility in the end after and imposition of responsibility or duty, are the necessities to obey Allah order and to leave the Allah prohibition. The natural tendency is a gift from Allah that guides the human being to the right path.